The Sources and Affecting Factors of Creep Threshold Stress of Magnesium Based Composite - Tian, J. (Проблемы прочности, 2016)
Tensile creep experiments were carried on AZ91D magnesium alloy and aluminum silicate short fiber reinforced AZ91D magnesium matrix composite. The creep threshold stress of AZ91D composite depends on the Al atoms solute atmosphere, the bearing and transferring force of short fiber. Threshold stress decreases with increasing temperature, increases with the increase of short fiber volume fraction and the load transfer coefficient , but the extent of increase decreases with the increase of the amount of β-Mg₁₇Al₁₂ precipitation phase. The load transfer coefficient α characterizes the bearing and transferring capabilities of short fibers. As a result, the mathematical model of threshold stress in the magnesium matrix composite is obtained.